2018
DOI: 10.1155/2018/8639173
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling of Antimalarial Agents by 3D-QSAR Study and Molecular Docking of Two Hybrids 4-Aminoquinoline-1,3,5-triazine and 4-Aminoquinoline-oxalamide Derivatives with the Receptor Protein in Its Both Wild and Mutant Types

Abstract: Modeling studies using 3D-QSAR and molecular docking methods were performed on a set of 34 hybrids of 4-aminoquinoline derivatives previously studied as effective antimalarial agents of wild type and quadruple mutant Plasmodium falciparum dihydrofolate reductase (DHFR). So, the famous mathematical method multiple linear regression (MLR) was explored to build the QSAR model. The DFT-B3LYP method with the basis set 6-31G was used to calculate the quantum chemical descriptors, chosen to represent the electronic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Molecular docking was performed by using default settings of Maestro v‐11.4. Selected proteins 1J3K , 3QG2 , and 3QGT were auto‐downloaded via software under the specific organism P. falciparum . The expression system of E. coli was performed under systematic steps, as follows: default setting and flexible space of ligands were validated by comparison of biological activity, and GlideScore, docking parameter, and best docked ligands were fit into the cavities with lower energy score.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking was performed by using default settings of Maestro v‐11.4. Selected proteins 1J3K , 3QG2 , and 3QGT were auto‐downloaded via software under the specific organism P. falciparum . The expression system of E. coli was performed under systematic steps, as follows: default setting and flexible space of ligands were validated by comparison of biological activity, and GlideScore, docking parameter, and best docked ligands were fit into the cavities with lower energy score.…”
Section: Resultsmentioning
confidence: 99%
“…The two compounds have the same radicals R1 and R2 but belong to different structural categories as it is detailed in paragraph 2.1. The reported study by Yuvanyama et al 33,10 has found the binding modes and has localized the active sites on both wild and mutant type of protein (Pf-DHFR). The study performed with a potent inhibitor 1,3,5-triazine derivative which is a preclinical molecule called WR99210.…”
Section: Docking Studiesmentioning
confidence: 99%
“…Herein, we report the molecular modeling of 4-anilinoquinoline-triazine derivatives 9 . In order to pursue, our ongoing research on molecular modeling of antimalarial activity 10 . We aim in this study to develop a predictive QSAR model, which will be used to analyze the antimalarial activity of a series of 41 hybrid 4-anilinoquinoline-triazine derivatives ( Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…azaaurone are very important therapeutic targets, as they show several biological activities including antimalarial activity [16,17]. TheTriazine derivative such as cycloguanil and chlorcycloguanil are already approved as antimalarial agents [18,19]. In this paper, we used the concept of hybrid molecules (T 14 -T 30), , in which two pharmacophores are linked together to increase their inhibitory activity against covid-19 [20].…”
Section: Introductionmentioning
confidence: 99%